ANALISIS KINERJA KEUANGAN DITINJAU DARI RASIO PROFITABILITAS PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Syafriont - -; Nur Fitriyaningsih (Jurnal Akademika, 2020)
This study aims to determine the development of financial performance in several food and beverage companies that go public on the Indonesia Stock Exchange from 2011-2015 whether it reflects good performance when viewed from the profitability ratio.Calculating the profitability ratio of a company requires the financial statements of the company concerned, which consists of the balance sheet and financial statement of income which shows the state of the company which consists of assets, debt and capital of the company at a certain time. To find out more about financial performance in several food and beverage companies that go public on the Indonesia Stock Exchange based on profitability ratio analysis, an analysis is used in the form of return on assets, return on equity, net profit margin, and gross profit margin from 2011-2015. The research method uses a qualitative descriptive approach. The analysis technique used is trend analysis. The company's performance in managing its finances in terms of profitability ratios is not efficient enough to run the company's operations.Keywords: Profitability Ratio, Financial Performance.